Preclinical evaluation of anti‐VEGFR2 monoclonal antibody ramucirumab labelled with zirconium‐89 for tumour imaging. (14th April 2021) - Novy, Zbynek; Janousek, Jiri; Barta, Pavel; Petrik, Milos; Hajduch, Marian; Trejtnar, Frantisek
Abstract : The key factors participating in angiogenesis include vascular endothelial growth factor (VEGF) and its receptors (VEGFRs), particularly VEGFR2. Angiogenesis suppression comprises the blocking of the VEGFR2 binding site by the monoclonal antibody ramucirumab (RAM). Our study focused on RAM radiolabelling with zirconium‐89 along with subsequent in vitro and in vivo biological evaluation. RAM was conjugated with the bifunctional chelator p ‐SCN‐Bn‐deferoxamine (DFO) and subsequently radiolabelled with [ 89 Zr]Zr‐oxalate. The binding affinity of [ 89 Zr]Zr‐DFO‐RAM to VEGFR2 was tested in vitro on prostate (PC‐3) and ovary adenocarcinoma (SK‐OV‐3) cell lines. The positron emission tomography/computed tomography (PET/CT) imaging and ex vivo biodistribution experiments were performed in PC‐3 and SK‐OV‐3 xenografted mice. The in vitro experiments revealed the preserved binding affinity of [ 89 Zr]Zr‐DFO‐RAM to VEGFR2. The obtained ex vivo biodistribution data showed the uptake in PC‐3 and SK‐OV‐3 tumours at about 8.7 ± 0.2 and 12.1 ± 1.6%ID/g, respectively. The tumour‐to‐muscle ratio for 1, 3 and 6 days post injection was 3.9, 5.5 and 5.12 for PC‐3 and 6.0, 8.0 and 8.82 for SK‐OV‐3 tumours, respectively. PET/CT images showed high radioactivity accumulation in the tumours starting already on the first day after tracer administration. The obtained results proved the potency of [ 89 Zr]Zr‐DFO‐RAM to target and image VEGFR2‐positive tumours in vivo. Abstract : [ 89 Zr]Zr‐DFO‐ramucirumab was prepared and tested in vitro and in vivo in this presented study. 89 Zr‐labelled ramucirumab demonstrated VEGFR2‐binding affinity in ovarian and prostate cancer cells in vitro. Moreover, positron emission tomography/computed tomography (PET/CT) imaging with [ 89 Zr]Zr‐DFO‐ramucirumab in xenograft tumour model in mice provided further evidence supporting its application as promising VEGFR2‐positive tumour imaging agent.